Inversion of Electrical Resistivity Data by VES Method for Water Exploring Case Study: South West of Iran - Alvandi, Ahmad; Babaei, Mojtaba (International Journal of Geography and Geology, 2014)
The purpose of this research is to explore the water in the south west of Hamedan which has many environmental problems and very few water resources. Also in the area, due to the lack of awareness, the farmers excavate the wells with high cost that results in declining water table. The collected data was investigated via the electrical probing at the Schlumberger array and Jointed with the wells data and geological information. The data processing was performed by conventional methods of calculation and utilized specialized software WINSEV, RES2D, RES3D, 2WIN at direct and inversion states. Finally the results of the research are acceptable and pleasant.